Reproductive impairment and intersexuality in Gomphina veneriformis (Bivalvia: Veneridae) by the tributyltin compound - Jung, Jun Park; Yun, Kyung Shin; Silas, S.O. Hung; Romano, Nick; Yong, Pil Cheon; Jae, Won Kim (Taylor & Francis, 2015)
A well-established xenoandrogen, tributyltin (TBT) causes sexual interferences in various animal models including gastropods. In bivalves, the disrupting effects of TBT on reproduction are largely unevaluated. In this study, we carried out a test on reproduction of the bivalve (Gomphina veneriformis) affected by TBT (0.4, 0.6, and 0.8 μg L−1). The experimental period was 36 weeks, starting in October during the inactive stage of the clam's reproductive cycle. The sex ratio (F:M) was 1:1.00 in the control group but changed to 1:1.37 in all the exposed groups with 0.8 μg L−1 TBT, leading to significantly higher values in male (1:1.54; P = 0.009). Gonadal maturity (ripe stage frequency) of males in the exposure groups was higher than females. The gonad index (GI) of females significantly decreased when exposed to 0.6 and 0.8 μg L−1 TBT. The prevalence of intersex was significantly different between males and females in all exposure groups, which became significantly different (P −1 after 36 weeks. These results suggest that TBT, a xenoandrogen, may lead to skewed sex ratio toward males, inhibit sexual maturation of the females, and also induce intersex in G. veneriformis as an imposex of gastropods. Therefore, reproductive indicators (sex ratio, gonadal development, and intersexuality) of bivalves may be used as useful bioindicators in monitoring marine pollution by TBT compounds.